ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN PAPAN MUSI DAN PAPER BAGIAN DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Malikal Mulki, Siti Tria; Sukma Mahemi, Ade; Sari Wijayanti, Ratna; Aghtiar Rakhman, Patra (Universitas Negeri Medan, 2024)
Difficulty in answering multiplication and division arithmetic operation questions and the absence of learning media in the learning process makes students' interest in learning less, so there is a need for tools in dealing with this. The purpose of this study was to determine the use of learning media on the musi board and paper division on students on the arithmetic operations of multiplication and division in mathematics learning. The research method used is descriptive qualitative with data collection techniques in this study, namely through observation, interviews, and documentation. The results showed that the use of music board media and paper parts on students on the operation of calculating multiplication and division in learning math is very effective. With the media of the musi board and paperbagian many students can work on multiplication and division operations easily but there are still 2 students who are lacking in working on multiplication and division operations researchers provide assistance by teaching how to work on media that is easy and can be learned by students so that these students can solve multiplication and division operations easily.